American philosophy before pragmatism - Goodman, Russell B. (Oxford history of philosophy., 2015)
Russell B. Goodman tells the story of the development of philosophy in America from the mid-18th century to the late 19th century. The key figures in this story, Jonathan Edwards, Benjamin Franklin, Thomas Jefferson, the writers of The Federalist, and the romantics (or 'transcendentalists') Emerson and Thoreau, were not professors but men of the world, whose deep formative influence on American thought brought philosophy together with religion, politics, and literature. Goodman considers their work in relation to the philosophers and other thinkers they found important: the deism of John Toland and Matthew Tindal, the moral sense theories of Francis Hutcheson, Adam Smith, and David Hume, the political and religious philosophy of John Locke, the romanticism of William Wordsworth and Samuel Taylor Coleridge, and the transcendental idealism of Immanuel Kant.-- Source other than Library of Congress.